Konsep Etika Pelajar dalam Membentuk Pendidikan Karakter Perspektif Kitab Ta”Limul Muta”Alim Karya Syeikh Burhanudin Az-Zarnuji - Mutiara Matondang; Rohimin Rohimin; Nurhidayat Nurhidayat (UIN Fatmawati Sukarno Bengkulu, 2024)
The type of research used in this study is Literature Research, the data collection technique is with Context Analysis of primary and secondary sources, the data analysis technique used is content analysis. Namely, describing the concept of the character in an orderly manner. The intention is that all ideas in Sheikh Az-Zarnuji's thoughts regarding moral education (character) are presented as they are. After that, the author compares them through the views of other relevant figures. Research results: (1) Sheikh Burhanudin Az-Zarnuji at Nu‟mân ibn Ibrâhîm ibn Khalîl az-Zarnûjî Tâj ad-Dîn is the person believed to be the only author of the Book of Ta‟līm Al-Muta‟allim. (2) Sheikh Burhanudin Az-Zarnuji mentioned that there are several ethics or morals that a student should have in seeking knowledge, namely the right intention, respecting teachers, respecting knowledge, choosing good friends, wara', tawakkal, avoiding sin and choosing the right knowledge and time to study. (3) In the book Ta'līm Al-Muta'allim Tharīq At-Ta'allum it can be implicitly understood that the concept of Character Education offered by Sheikh Burhanudin Az-Zarnuji is in the form of religious character, discipline, hard work, creativity, curiosity, independence, love of reading and responsibility. (4) The book Ta'līm Al-Muta'allim by Az Zarnuji is very relevant to character values if used as a reference or guideline in the world of education, especially Islamic education today, because this book discusses moral education which is very relevant today.